ACCESS TO JUSTICE OF CHILDREN WITH DISABILITIES IN DEFILEMENT CASES IN MALAWI (African Disability Rights Yearbook, 2021)
The sexual abuse of children with disabilities is a serious problem in society requiring responses tailored to meet their unique needs. In most cases such abuses remain unreported and, if reported, the children face many challenges to accessjustice within the criminal justice system. This article aims at examining in detailthe legal treatment of cases involving children with disabilities in defilement offences in Malawi. The article will attempt to answer the question of whether Malawirespects the rights to access justice of children with disabilities, provided for in various international instruments as well as in local statutes, including article 13 of the CRPD and section 41 of Constitution of Malawi. The right to access justice refersto the ability of people to seek and obtain a remedy through formal and informal justice institutions, and in conformity with human rights standards. The articleanalyses the ability of children with disabilities in defilement offences to seek and obtain a remedy through formal institutions of justice. The article further analyses the legal and social barriers available to children with disabilities in defilement cases to access the formal systems and structures of the law. In so doing, the articleexamines four components of the right to access justice as areas of focus, namely, access to information; legal representation; a child’s ability to participate in legal proceedings; and the availability of appropriate training of relevant professionals in the field of criminal justice. It is argued that, achieving access to justice for children with disabilities requires comprehensive social and legal support, as well as a constant analysis of legal structures in place that make it more difficult for childrenwith disabilities in defilement cases to be empowered by the law.
Keywords: sexual abuse; children with disabilities; justice; criminal justice system; legal treatment; Malawi; international instruments; local statutes; article 13 of the CRPD; section 41 of Constitution of Malawi; human right standards; informal justice institution; criminal justice; law; legal